Penanaman Nilai-Nilai Pancasila Sebagai Upaya Pencegahan Terhadap Penyalahgunaan Narkoba Pada Masyarakat Desa Kuti Agung Kabupaten Seluma - Achmad Megantara; Syafryadin Syafryadin (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2022)
This socialization basically aims to provide information and knowledge to the community, especially teenagers in an effort to face the development of a free era. The implementation of the work program is divided into two, namely conducting socialization about the impact of drug abuse in legal aspects and competitions regarding the inculcation of Pancasila values. Also make pamphlets about the impact of drug abuse. By making pamphlets about the impact of drug abuse given to the community to be read repeatedly. This socialization is expected to be useful for preventing drug abuse itself, as well as improving the quality of human resources.